Pengelolaan Bank Sampah Untuk Kesejahteraan Masyarakat di Kelurahan Sungai Miai Kecamatan Banjarmasin Utara - Wahyuning Minawati; Dewi Rahayu (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to find out how the management of the garbage bank in Sungai Miai Sub-district, North Banjarmasin District, and how community empowerment in managing the waste bank in Sungai Miai Sub-district, North Banjarmasin District. In this study, researchers used a qualitative descriptive method. Data sources used are primary and secondary data that help complete research data, with data collection techniques through interviews, observation, and documentation.            This study indicates that the management of the waste bank is quite effective in improving the welfare of the active community and the management of the waste bank. Still, it is less effective for the community or ordinary housewives. Active communities get garbage not only from households but also from businesses they have, so the amount of waste generated is quite large. In community empowerment, the learning process takes place, which is carried out in stages to achieve independence; there are three stages, namely the awareness stage, the transformation stage of the abilities, and the stage of intellectual capacity enhancement through the socialization and training activities carried out by the garbage bank.            Some of the obstacles that occur in this study are garbage banks that are less active in limiting researchers in getting information and ordinary informants who provide less information, and informants who are less open. A garbage bank is currently a place for the community to collect garbage that can still be used and provide benefits. It is expected that in the future, the garbage bank program can develop and can accommodate the waste that is disposed of in vain without any economic value.